1996
DOI: 10.1002/(sici)1520-6793(199601)13:1<77::aid-mar5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

The Aad-Ab-PI relationship in children: The impact of brand familiarity and measurement timing

Abstract: Given the explosion of research in the past decade that has examined the Aad‐Ab‐PI relationship using adult subjects, one would expect to see an almost parallel stream of research involving children. However, as is evident in Brown and Stayman's (1992) meta‐analysis of the literature, no studies investigating this area have used children as the sample. This study provides an initial exploration into the Aad‐Ab‐PI relationship in children with specific focus given to the impact of brand familiarity and measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
1
19

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 37 publications
1
105
1
19
Order By: Relevance
“…PI also indicates how likely it is that the individual would purchase a product (Phelps & Hoy, 1996). Many previous studies have used (PI) as a dependent variable Yi, 1990;Saliagas, & William, 1987;Machleit & Wilson, 1988).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…PI also indicates how likely it is that the individual would purchase a product (Phelps & Hoy, 1996). Many previous studies have used (PI) as a dependent variable Yi, 1990;Saliagas, & William, 1987;Machleit & Wilson, 1988).…”
Section: Introductionmentioning
confidence: 89%
“…The advertising effect models can be found in studies such as Goldsmith et al (1999;2000;2001; and Shimp and Gresham (1985). Attitude toward brand (Ab) is defined as a predisposition to respond in a favourable or unfavourable manner to a particular brand after the advertising stimulus has been shown to the individual (Phelps and Hoy, 1996). Previous studies indicated that (Aad) and (Ab) are not considered as one variable as they are different from each other, and had been used as separated variables (e.g.…”
Section: The Relationship Between Attitude Toward Advertisement (Aad)mentioning
confidence: 99%
See 3 more Smart Citations